Empowerment-based case management for treatment-resistant schizophrenia: a three-year single case report - Wang, Cong; Li, Xianbin; Chen, Jinsong; Li, Xiaohong; Hou, Wenpeng; Dong, Ning (Frontiers in Psychiatry, 2026)
This case report describes the implementation and observed outcomes of an empowerment-oriented case management approach in a patient with treatment-resistant schizophrenia (TRS), addressing the limitations of conventional approaches that often neglect patient autonomy and subjective agency. Through the implementation of a multidisciplinary, four-dimensional empowerment framework—comprising pathological treatment, psychological cognition, social engagement, and family care—a 34-year-old male TRS patient received targeted intervention over a three-year period. Quantitative assessments, including PANSS, HRSD, SDSS, CGI, MRSS, and FAES II-CV, demonstrated substantial improvements: PANSS total score decreased from 90 to 61, CGI severity score reduced from 6 to 3, and MRSS dependency subscale declined from 29 to 14. Qualitative interviews further revealed enhanced medication adherence, symptom self-monitoring, and social functioning, alongside increased daily autonomy, reduced stigma, and improved family dynamics. These preliminary observations from a single case suggest potential benefits that warrant systematic investigation through controlled studies. The temporal associations observed between the intervention and improvements cannot establish causality but provide hypotheses for future research.